Backbone‐Bridging Promotes Diversity in Heteroleptic Cages - Wu, Kai (Angew Chem Int Ed Engl, 2020)
The combination of shape‐complementary bis‐monodentate ligands L(A) and L(B) with Pd(II) cations yields heteroleptic cages cis‐[Pd(2) L(A) (2) L(B) (2)] by self‐sorting. Herein, we report how such assemblies can be diversified by introduction of covalent backbone bridges between two L(A) units. Together with solvent and guest effects, the flexibility of these linkers can modulate nuclearity, topology, and number of cavities in a family of four structurally diverse assemblies. Ligand L(A1), with flexible linker, reacts in CH(3)CN with its L(B) counterpart to a tetranuclear dimer D1. In DMSO, however, a trinuclear pseudo‐tetrahedron T1 is formed. The product of L(A2), with rigid linker, looks similar to D1, but with a rotated ligand arrangement. In presence of an anionic guest, this dimer D2 transforms and a hexanuclear prismatic barrel P2 crystallizes. We demonstrate how controlling a ligand's coordination mode can trigger structural differentiation and increase complexity in metallo‐supramolecular assembly.